Anaerobic Treatment Of Fresh Leachate From Transfer Station - Dara Ghasimi, Seyed Mohammad (2008)
One stage anaerobic digestion was carried out in this study where fresh leachate from Taman Beringin Transfer Station was used as a substrate to be treated in terms of chemical oxygen demand (COD) removal by using 10 L stirred tank reactor (STR) within period of two and three months for semi-continuous and batch anaerobic treatment processes, respectively, in which the maximum loading rate of the system was tested at 6kg COD/m3.day. Palm oil mill effluent (POME) sludge was used as an inoculum in phase 2 in order to obtain high amount of COD removal. Three experiments were conducted in anaerobic treatment of fresh leachate until steady state was achieved, i.e. (1) no seed was added and pH and temperature were not controlled (phase1); (2) POME sludge was used as an inoculum and no pH adjustment and temperature control was done, fresh leachate was fed in semi-continuous mode and hydraulic retention time (HRT) 10 days was selected (phase2, run1); (3) POME sludge was used as an inoculum, pH was adjusted by using Sodium Hydroxide (NaOH) and temperature was not controlled and HRT 10 days was chosen (phase 2, run 2).In general, anaerobic digestion using POME seed sludge shows better efficiency in COD reduction and biochemical oxygen demand (BOD5 ) in comparison to batch process and unadjusted pH in run 1 which has been obtained in this study. The initial values for both COD and BOD5 of fresh leachate were extremely high compared with the stabilized landfill leachate. COD reduction rate for the batch (phase 1) and semi-continuous process (phase 2, run1 & 2) experiments were found 43, 37 and 52.7 % for period of 91, 27 and 30 days, respectively. These results clearly show that using seed sludge as an inoculum as well as pH adjustment indicated better efficiency in terms of COD removal in comparison to phase 1 and run1 (unadjusted pH). Maximum reduction in BOD5 occurred in run 2 (pH adjusted) with more than 90 % and 80-85 % for batch process at two ending points; day 53 and 91, respectively. The volatile fatty acid (VFA) concentration was a rapid indicator of the reactor’s stability. High concentration of VFA indicated that the reactor was unstable. It was apparent that as the total VFA concentration rose, the microbial population’s ability to utilize these compounds effectively was inhibited. The major acids produced were acid acetic (HAc), propionic (HPr) and butyric acids (HBu). The levels of HAc acid and HPr appeared to be the VFA species that accumulated and started to cause an imbalance in the reactor. Acetic and propionic acid have been accumulated in run 2 and their concentration increased to 39 and 5 % respectively, while n-butyric decreased about 46% in comparison to day 27 in run 1. All these cases show that anaerobic treatment in run 2 has been subjected to failure. In this study it was also found that with decrease in pH, decrease in amount of COD removal and increase in total volatile fatty acids (TVFA) was detected for run 1. TVFA was indicated at a range of 6000-9000 mg/L and 9000-10000 mg/L for run 1 and 2,respectively, which showed despite of adjusting pH above 7 still considerable accumulations of VFA was observed in the bioreactor. Therefore, it was concluded that the methanogenic population has not reached sufficient level to convert the organic acids produced from the acidogenic bacteria.